Associations between changes in leg extensor muscle power and physical function after supervised exercise in patients with hip osteoarthritis. Secondary analysis from the hip booster trial - Troels Kjeldsen; Ulrik Dalgas; Søren T. Skou; Frederik N. Foldager; Bo M. Bibby; Inger Mechlenburg (Osteoarthritis and Cartilage Open)
Objective: To investigate associations between changes in leg extensor muscle power of the affected limb (ΔLEP) and changes in physical function after 12 weeks of progressive resistance training (PRT) or neuromuscular exercise (NEMEX) in patients with hip osteoarthritis. Design: Secondary analyses of a randomized controlled trial. From 160 participants enrolled in the clinical trial and cluster randomized to PRT (n ​= ​82) or NEMEX (n ​= ​78), a total of 147 (92%) had complete follow-up data and were included in the analyses. Simple linear and multivariate linear regression models estimated the crude and adjusted associations between ΔLEP normalized to body weight (watt/kg) and changes in performance-based and patient-reported measures of physical function. Results: Adjusted estimates [95% confidence intervals] showed associations between ΔLEP (watt/kg) and changes in 30-s chair stand test (β: 2.34 [1.33; 3.35], R2: 0.13), 9-step timed stair climb test (β: −1.47 [-2.09; −0.85], R2: 0.38), 40-m fast paced walking test (β: −2.20 [-3.30; −1.11], R2: 0.09), Activities of Daily Life function (β: 8.63 [3.16; 14.10], R2: 0.23) and Sport and Recreation function (β: 10.57 [2.32; 18.82], R2: 0.21) subscales from the Hip disability and Osteoarthritis Outcomes Score. Group allocation to PRT did not lead to greater regression coefficients than in NEMEX. Conclusions: Changes in leg extensor muscle power after supervised exercise are consistently associated with changes in physical function across performance-based and patient-reported measures in patients with hip osteoarthritis. These associations seem to be independent of allocation to PRT or NEMEX.